Prechemotherapy neutrophil : lymphocyte ratio is superior to the platelet : lymphocyte ratio as a prognostic indicator for locally advanced esophageal squamous cell cancer treated with neoadjuvant chemotherapy. Issue 5 (27th January 2015) - Ji, W. H.; Jiang, Y. H.; Ji, Y. L.; Li, B.; Mao, W. M.
Summary: The study aimed to evaluate the prognostic significance of prechemotherapy neutrophil to lymphocyte ratio and platelet to lymphocyte ratio, and preoperative neutrophil to lymphocyte ratio and platelet to lymphocyte ratio in locally advanced esophageal squamous cell cancer. We analyzed retrospectively locally advanced esophageal squamous cell cancer patients who had received neoadjuvant chemotherapy before undergoing a radical esophagectomy between 2009 and 2012. Neutrophil to lymphocyte ratio and platelet to lymphocyte ratio before chemotherapy and before the surgery were calculated. Univariate analyses showed that prechemotherapy neutrophil to lymphocyte ratio >5 ( P = 0.048, hazard ratio = 2.86; 95% confidence interval: 1.01–8.12) and prechemotherapy platelet to lymphocyte ratio >130 ( P = 0.025, hazard ratio = 5.50; 95% confidence interval: 1.23–24.55) were associated significantly with overall survival (OS), and prechemotherapy platelet to lymphocyte ratio >130 ( P = 0.026, hazard ratio = 3.18; 95% confidence interval: 1.15–8.85) was associated significantly with progression‐free survival. However, only prechemotherapy neutrophil to lymphocyte ratio >5 ( P = 0.024, hazard ratio = 3.50; 95% confidence interval: 1.18–10.40) remained significantly associated with OS in multivariate analyses. Neither preoperative neutrophil to lymphocyte ratio nor platelet to lymphocyte ratio was associated with OS or progression‐free survival. The prechemotherapy neutrophil to lymphocyte ratio >5 to preoperative neutrophil to lymphocyte ratio ≤5 group showed significantly worse OS than the prechemotherapy neutrophil to lymphocyte ratio ≤5 to preoperative neutrophil to lymphocyte ratio ≤5 group ( P = 0.050). The prechemotherapy platelet to lymphocyte ratio >130 to preoperative platelet to lymphocyte ratio ≤130 group ( P = 0.016) and platelet to lymphocyte ratio >130 to preoperative platelet to lymphocyte ratio >130 group ( P = 0.042) showed significantly worse OS than the prechemotherapy platelet to lymphocyte ratio ≤30 to preoperative platelet to lymphocyte ratio ≤130 group. In conclusions, prechemotherapy neutrophil to lymphocyte ratio is an independent prognostic factor for OS in patients with advanced esophageal squamous cell cancer treated with neoadjuvant chemotherapy, and, as an adverse prognostic predictor, increased prechemotherapy neutrophil to lymphocyte ratio is superior to platelet to lymphocyte ratio. Maintaining a low neutrophil to lymphocyte ratio and platelet to lymphocyte ratio throughout treatment is a predictor of better OS.